Identifying Biomarkers from Transcriptomic Signatures in Renal Allograft Biopsies Using Deceased and Living Donors - Yang, Bin; Sylvius, Nicolas; Luo, Jinli; Yang, Cheng; Da, Zhanyun; Crotty, Charlottelrm; Nicholson, Michael L. (Frontiers in Immunology, 2021)
The survival of transplant kidneys using deceased donors (DD) is inferior to living donors (LD), in which underlying mechanisms and potential interventions need to be imperatively investigated. In this study, the microarray analysis of 24 human kidney biopsies paired at 30 minutes and 3 months post-transplantation using DD and LD. A different transcriptomic profile was revealed between two time points regardless of donor types. There were 446 differentially expressed genes (DEGs) between DD and LD at 30 minutes and 146 DEGs at 3 months, with 25 DEGs in common. These DEGs reflected donor injury and acute immune responses associated with inflammation and cell death as early as at 30 minutes, which could be a precious window of potential intervention. DEGs at 3 months mainly represented the changes of adaptive immunity, immunosuppressive treatment, remodeling or fibrosis via different networks and signaling pathways. To identify biomarkers, 20 highly DEGs involved in kidney diseases, as well as 10 DEGs at 30 minutes correlated with renal function and histology at 12 months, were further validated by quantitative polymerase chain reaction (qPCR) in 24 microarray analyzed samples and additional 33 time point unpaired allograft biopsies. The qPCR revealed that, in DD, up-regulated SERPINA3, SLPI and CBF at 30 minutes, FTCD and TASPN7 at both time points; at 3 months up or down-regulated SERPINA3 in LD or DD, increased VCAN and TIMP1 with decreased FOS in both donors. Taken together, divergent transcriptomic signatures between DD and LD, and changed by the time post-transplantation, might contribute to different allograft survival of two type kidney donors. Some DEGs such as FTCD and TASPN7 could be novel biomarkers not only for timely diagnosis, but also early precise genetic intervention at donor preservation, implantation and post-transplantation, in particular for effectively improving the quality and survival of DD.